PERSEPSI SISWA TERHADAP PEMBELAJARAN SIMPLE PRESENT TENSE MENGGUNAKAN ALAT PERMAINAN LEGO SEBAGAI MEDIA PEMBELAJARAN - Ni Luh Desy Suari Dewi; Gek Wulan Novi Utami; I Gede Neil Prajamukti Wardhana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
English teachers are looking for means to make English tenses easier learnt by students. Good teaching methods with appropriate media will trigger students' motivation to learn English. One of the methods that have been tested in English teaching research is the Silent Way method. This method commonly uses Fidel Chart, Word Chart and Rod. Nevertheless, based on the study in this article, the media were replaced by using Lego. The purpose of the study is to determine the perception of English learners on the use of Lego as a learning tool of the Simple Present Tense. According to the study, EFL learners who ranged from 14 to 17 years old that joined semi-private and English courses group in the North Kuta area filled out the questionnaire to provide their perception of Lego in the learning process. Students' perceptions of the Simple Present Tense learning by using Lego were obtained by providing a questionnaire with the fastened statement by using a Likert scale. The results indicated that a number of 80% of students experience strongly agree, 20% of students experienced agreed, 0% hesitated, 0% disagreed, and 0% strongly disagreed with the application of lego in the simple present tense learning process. Thus, it could be summarized that students provided a positive perception on the application of Lego as a tool for Simple Present Tense learning.